Speeding up, down the hill: how the EU shapes corporate tax competition in the single market - Philipp Genschel; Achim Kemmerling; Eric Seils (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2008)
We show that tax competition in the EU is shaped by four interrelated institutional mechanisms: 1) Market integration, by reducing the transaction costs of cross-border tax arbitrage in the Single Market, 2) enlargement, by increasing the number and heterogeneity of states involved in intra-EU tax competition, 3) tax coordination, by restricting the range of competitive instruments at the disposal of governments, and 4) supranational judicial review by limiting the scope of unilateral defences against tax competition (judicialization). As a consequence, tax competition is significantly stronger in the EU, and the race to the bottom in corporate tax rates more pronounced than in the rest of the world. – – Wir zeigen, dass der Steuerwettbewerb in der EU durch vier miteinander zusammenhängende institutionelle Mechanismen gestaltet wird: 1) Die Marktintegration verringert die Kosten der Steuerarbitrage im Binnenmarkt. 2) Die Osterweiterung erhöht die Zahl und Heterogenität der Länder, welche am Wettbewerb in der EU beteiligt sind. 3) Steuerkoordination beschränkt die Auswahl der Mittel, auf welche die Regierungen im Wettbewerb zurückgreifen können. 4) Die Rechtsprechung des EUGH reduziert die Möglichkeiten der Nationalstaaten sich unilateral gegen den Steuerwettbewerb zu verteidigen. Deshalb ist der Steuerwettbewerb in der EU stärker als im Rest der Welt, und die Körperschaftssteuersätze fallen dementsprechend schneller als andernorts.
Keywords: 330; Unternehmensbesteuerung; Steuerwettbewerb; EU-Steuerrecht; EU-Staaten